2011
DOI: 10.4103/0973-7847.79093
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids: A versatile source of anticancer drugs

Abstract: An exponential increase in the number of studies investigating how different components of the diet interact at the molecular and cellular level to determine the fate of a cell has been witnessed. In search for anticancer drugs compelling data from laboratories, epidemiologic investigations, and human clinical trials showed that flavonoids have important effects on cancer chemoprevention and chemotherapy. In many molecular mechanisms of action for prevention against cancer, flavonoids play a major role by inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
146
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(149 citation statements)
references
References 74 publications
1
146
0
2
Order By: Relevance
“…They generally have a sixteen-carbon skeleton and the structures vary around the heterocyclic oxygen ring [59]. Research has shown that flavonoids inhibit cell proliferation and angiogenesis, cause cell cycle arrest, induce cell apoptosis, and reverse multi-drug resistance and/or a combination of the aforementioned mechanisms [60]. …”
Section: Traditional Chinese Medicines (Tcms) As Anti-cancer Agentsmentioning
confidence: 99%
“…They generally have a sixteen-carbon skeleton and the structures vary around the heterocyclic oxygen ring [59]. Research has shown that flavonoids inhibit cell proliferation and angiogenesis, cause cell cycle arrest, induce cell apoptosis, and reverse multi-drug resistance and/or a combination of the aforementioned mechanisms [60]. …”
Section: Traditional Chinese Medicines (Tcms) As Anti-cancer Agentsmentioning
confidence: 99%
“…Although polyphenols illustrate a wide range of biological activities in vitro, their low bioavailability attenuates their efficacy in vivo [104,105]. Despite the fact that they are the most common in human diet, their activity is not always in parallel with their abundance, either because of poor absorption or rapid elimination [106].…”
Section: Carob’s Polyphenols and Bioavailabilitymentioning
confidence: 99%
“…These compounds are also a component of disease treatment (phytotherapy), as they are present in the seeds, stems, barks, roots, and/or flowers of several medicinal plants [78]. Flavonoids have shown a wide range of therapeutic properties in clinical and preclinical studies, including, but not limited to, antioxidant, anticancer, antiinflammatory, and antiallergy activities [7982]. Luteolin, a widely distributed flavonoid, has been reported to exhibit anti-inflammatory, antioxidant, and anticarcinogenic activities [83].…”
Section: Introductionmentioning
confidence: 99%